2004
DOI: 10.1099/vir.0.80133-0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of foot-and-mouth disease virus replication by small interfering RNA

Abstract: Foot-and-mouth disease, caused by foot-and-mouth disease virus (FMDV), is one of the most dangerous diseases of cloven-hoofed animals and is a constant threat to the dairy and beef industries in the Middle East and other regions of the world, despite intensive vaccination programmes. In this work, the ability of specific small interfering (si)RNAs to inhibit virus replication in BHK-21 cells was examined. By using bioinformatic computer programs, all FMDV sequences in public-domain databases were analysed. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 27 publications
1
50
1
Order By: Relevance
“…Their study showed that microinjection of antisense DNA or RNA targeting the AUG2 region into the cytoplasms of BHK-21 cells caused transient inhibition of FMDV infections. The magnitude of viral inhibition produced by FMDV-specific PPMO compares quite favorably with results from studies with other nucleic-acid-based agents evaluated against FMDV, such as small interfering RNA (8,10,19,21,25), antisense DNA (18), and antisense RNA (3,17).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Their study showed that microinjection of antisense DNA or RNA targeting the AUG2 region into the cytoplasms of BHK-21 cells caused transient inhibition of FMDV infections. The magnitude of viral inhibition produced by FMDV-specific PPMO compares quite favorably with results from studies with other nucleic-acid-based agents evaluated against FMDV, such as small interfering RNA (8,10,19,21,25), antisense DNA (18), and antisense RNA (3,17).…”
Section: Discussionmentioning
confidence: 52%
“…Sense and antisense RNAs (3,17,18,34), antisense DNA (18), and small interfering RNA (8,10,19) have generated various levels of antiviral activity. All of these strategies apparently function by interfering with expression of the viral RNA genome.…”
mentioning
confidence: 99%
“…A number of compounds designed to inhibit picornavirus infections through an antisense-mediated mechanism have generated positive preclinical results but are still early in the development process. Antisense phophorothioate DNA has been used against coxsackievirus type B3 (CVB3) in vitro (57) and in vivo (62), antisense RNA has been used against foot-and-mouth disease virus (45), and small interfering RNA has been used against several picornaviruses (3,20,21,26,42,47), all with some success. Phosphorodiamidate morpholino oligomers (PMO) are composed of individual subunits consisting of a DNA base connected to a morpholine ring and phophorodiamidate-linked backbone (50).…”
mentioning
confidence: 99%
“…RNAi is an effective method for inhibiting viral replication, and previous studies have investigated the effects of anti-viral RNAi methods on FMDV (29,30). The initial stage of host cell infection by FMDV involves interaction with a cognate cell-surface receptor, which subsequently enables virus particles to enter cells in a receptor-mediated manner.…”
Section: Discussionmentioning
confidence: 99%